Gambian Mothers Lack Obstetric Danger Sign Knowledge, But Educational Intervention Shows Promise - Kara Shannon; Jocelyn Burridge; Brodus Franklin; Sheena Bhushan; Susan Hilsenbeck; Elena V. Petrova; James N'Dow; Ibezimako Iwuh; Sharmila Anandasabapathy; Jeffrey P. Wilkinson (Ubiquity Press, 2024)
Background: The Gambia has the 12th highest maternal mortality rate in the world, with 80% of deaths resulting from avoidable causes. Unawareness of pregnancy danger signs (DS) has been shown to be a barrier to seeking obstetric care, while app-based education intervention has shown promise. Objective: We aim to assess patient awareness of DS, identify barriers to awareness, and evaluate potential for implementing smartphone-based technologies for education. Methods: A cross-sectional semi-structured survey was administered to Gambian women (n = 100) across five hospitals/health centers. Data and informed consent were collected via an online survey portal. Analysis included bivariate analysis and descriptive statistics with p < 0.05 significance level. Recall of 0-2 DS per category was classified as "low" knowledge, 3-5 as "moderate" knowledge, and 6+ as "sufficient" knowledge. Cross-category recall was quantified for overall awareness level (0-6 = "low", 7-12 = "moderate", 13+ = "sufficient". N = 28 total DS). Findings: Although 75% of participants (n = 100) self-perceived "sufficient" knowledge of DS, the average recall was only two (SD = 2, n = 11) pregnancy DS, one labor and delivery DS (SD = 1, n = 8), and one postpartum DS (SD = 1, n = 9). Twenty-one women were unable to recall any danger signs. "Low" awareness was identified in 77% of women, while 23%, and 0% of women showed "moderate" and "sufficient" overall awareness, respectively. Education level was significantly correlated with overall danger sign recall (ρ(98) = .243, p = .015) and awareness level (ρ(98) = .265, p = .008). Monthly income was significantly correlated with awareness level (ρ(97) = .311, p = .002). Smartphone ownership was reported by 76% of women, and 97% expressed interest in using app-based video (94%) or provider (93%) teaching. Conclusions: Women had low knowledge of obstetric danger signs, and true awareness of danger signs was remarkably lower than self-perceived knowledge. However, patients exhibited proper healthcare-seeking behavior when danger signs arose. Findings suggest that video- or messaging-based education from local healthcare providers may be effective DS educational interventions.